Thyroid hormones and their membrane receptors as therapeutic targets for T cell lymphomas - Cremaschi, Graciela A. (2016)
Fil: Cremaschi, Graciela A. Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina